Edukasi Berpengaruh terhadap Pencegahan Penyakit Menular Seksual pada ABK - Umagapi, Fitria; Sianay, Herlien; Lating, Zulfikar; Wally, Dinda Aprianda; Lapodi, Abd Rijali (Wiraraja Medika : Jurnal Kesehatan, 2025)
Sexually transmitted infections are infections that appear or are spread from one individual to the next from vaginal, oral and anal sex. The incidence of STIs which is still quite high is caused by risk factors of more than one sex partner, marital status, condom use, PSK, Homosexuality, last sexual partner, and history of suffering from STIs. The purpose of this study was to provide in-depth information to crew members (ABK) as a means of increasing self-awareness through education of sexually transmitted diseases on knowledge of prevention in crew members at the Hurnala Tulehu port. using the Pre-experiment method with the One Group Pre-test Post-test type. The treatment activity provided was health education on knowledge of prevention of sexually transmitted diseases in crew members (ABK) with the one group pre-test-post-test method. This method uses one group as the subject of the study with observations before and after the intervention or action was carried out. This was done to compare the knowledge of ABK before and after being given treatment (intervention) with a sample size of 113 samples. The results of the statistical test show that the p value = 0.002 < 0.050, which means that there is a relationship between knowledge and preventive measures for sexually transmitted diseases in crew members (ABK) influenced by several factors, including predisposing factors, namely the knowledge of crew members (ABK) who are in the poor category have not carried out prevention properly and knowledge about sexually transmitted diseases is still minimal.